Waves and Radiation: Television Sets and the Fear of Biological Harm in the Cold War. - Stamm, Michael (Historical Journal of Film, Radio & Television, 2025)
This article explores how anxiety about the possible radioactivity of media devices became a part of American life in the atomic age. The initial impetus came in the late 1960s, when a panic erupted over the possibility that as many as five percent of American color television sets were emitting hazardous levels of radiation. In response, Congress undertook a series of investigations, the findings from which became part of the Radiation Control for Health and Safety Act of 1968, one of a suite of transformative environmental policies enacted during the Johnson and Nixon administrations. This panic was an important part of television history, and it formed the basis of concerns about radiation and the health effects of electronic devices that persisted throughout the Cold War. For many Americans, television sets became material objects onto which they could project anxieties about technology, interconnection, and the atomic age. In expressing varying degrees of panic about radiation emanating from their televisions, Americans articulated a vision of media showing how many understood their effects to be not just social but biological.